THE WEARING OF THE HEADSCARF – THE PLIGHT OF MUSLIM WOMEN: A BRIEF COMPARATIVE SYNOPSIS - Marita Carnelley; Waheeda Banoobhai (Obiter, 2022)
In 2002 Prof JMT Labuschagne published a South African legal perspective on the Muslim headscarf entitled “Die Regsstatus van die Islamkopdoek: Opmerkinge Oor die Begrensing van Religieuse Simbole en Gebruike in die Regstaat” (2002 17 SA Public Law 382). In this note he referred to the legal solutions regarding the wearing of a headscarf and other religious symbols in two European countries, Germany and Switzerland, and noted that a distinction is generally made between the wearing of religious symbols in the private and public spheres with specific reference to educational institutions. He concluded that in these countries the freedom of religion, belief and opinion is one of the cornerstones of a democratic society and that there is a duty on society to be tolerant towards divergent views to ensure social peace; and that this also applies in an educational environment. However, the majority of courts, with regard to the headscarf in the public domain, require that teachers especially must be seen to be strictly neutral, making the wearing of the headscarf in a public school unacceptable. The aim of this note is to provide an update on Germany, one of the jurisdictions discussed by Labuschagne; to expand the comparative view to other jurisdictions that have also grappled with the issue; and to set out the South African legal position. Before the South African legal situation is discussed, the position in other jurisdictions is described. With regard to the wearing of the headscarf at educational institutions, be it schools or universities, the situation in Singapore, Turkey, France, Germany and England is of comparative interest, whilst regarding the wearing thereof at work, the French and German solutions are considered. For reasons to become clear subsequently, this distinction in South Africa is not of particular importance as the same legal principles are applicable to both scenarios.